تأثیر استخدام التعلم الاتقاني في تعلم مھارتي الطبطبة والتصویب بكرة الید - حاتم شوكت ابراهيم; رافد حبيب قدوري; عبدالكريم ابراهيم جاسم (physical education and sport sciences college for women/ Baghdad University, 2017)
The research aims to identify the impact of learning Alleghany in learning tow skills clapotement and correction reel hand. And researchers have adopted the experimental method for suitability and the nature of the search, the research community of students from the second phase of study at the Faculty of Physical Education and Sports Science in Diwali University for the academic year 2015- 2016's ( 280) students. The research sample consisted of students Division (f) havebeen selected from among the people of school year second's (6) people, and at a rate of (25-35) called for each division, and this amounted to the sample (30), student, and the sample exploratory experiments being researchers working on totaling 10 students were from the Division (d) after the researchers that ruled out a number of students from the research sample, has homogenization process between the two groups of the research sample to adjust the following chronological age, height and weight variables, was parity with between the two sets of research in learning my skills clapotement and correction hand reel, and the art teacher to apply the curriculum of the College has been organizing exercises and repeat them on the use of style Alleghany learning the experimental group the control group used the technique, and the curriculum took (12) educational unit and by (2) unit learning per week for each group, and that the educational unit time (90 minutes), was the use of the user's program in the areas of statistics and system (spss) to extract the data for research. Thus, the researchers recommend following the emphasis on the use of style Alleghany in the educational process in learning the basic skills hand reel. As well as the dissemination of research material on a school handball results for the purpose of adoption in the educational process. And emphasize the need to use more than one method in the educational process and to move away from traditional methods